Role of nursing care after retinoblastoma surgery in children: A narrative review - Mobina Tohidian (Journal of Nursing Reports in Clinical Practice)
Retinoblastoma emerges as the predominant intraocular malignancy during childhood. Surgical interventions address specific clinical situations, balancing tumor regression and visual functionality. Also, nurses play a pivotal role in preoperative preparations, intraoperative support, and postoperative care, contributing to the child's physical and emotional well-being. The study aims to comprehensively review nursing care post-retinoblastoma surgery, providing an educational and research foundation in pediatric oncology. A literature review on nursing care after retinoblastoma surgery utilized diverse databases and keywords. Searches spanned Persian (Magiran and Scientific Information Database), international databases including PubMed and Google Scholar search engine, employing Boolean operators. Initially, 120 articles underwent screening, resulting in 9 meeting the criteria after eliminating duplicates. Nursing care following retinoblastoma surgery is a meticulous and multifaceted process aimed at ensuring the child's holistic well-being and triumphant recovery. The three key focus areas include surgical site care, pain management, and complication monitoring. Surgical site care involves vigilant oversight, prompt reporting of concerns, and meticulous attention to the healing process. Pain management strategies, tailored to the child's age, involve medication and non-pharmacological methods, enhancing overall well-being. Proactive monitoring for complications encompasses regular assessments of vital signs and visual changes, emphasizing effective communication within the healthcare team. The comprehensive follow-up care extends beyond immediate concerns, addressing medical evaluations, visual assessments, psychosocial support, educational guidance, and lifestyle considerations. This approach ensures a thorough and successful postoperative journey for the child. Nursing care after retinoblastoma surgery is vital for children's recovery. The holistic approach involves meticulous surgical site management, personalized pain relief, proactive complication monitoring, and comprehensive follow-up care. Effective communication and collaboration ensure tailored support for each child, emphasizing a patient-centric approach for a successful postoperative journey.